2006
DOI: 10.1016/s1470-2045(06)70699-4
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of radiotherapy fraction size on tumour control in patients with early-stage breast cancer after local tumour excision: long-term results of a randomised trial

Abstract: SummaryBackground Standard curative schedules of radiotherapy to the breast deliver 25 fractions of 2·0 Gy over 5 weeks. In a randomised trial, we tested whether fewer, larger fractions were at least as safe and as eff ective as standard regimens. In this analysis, we assessed the long-term results of tumour control in the same population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
356
0
26

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 542 publications
(391 citation statements)
references
References 8 publications
9
356
0
26
Order By: Relevance
“…Change in photographic breast appearance at 2 years was used to define the late adverse effect caused by radiotherapy in this study. This endpoint has been well established and validated in randomised clinical trials, indicating it to be sensitive to small (<10%) differences in randomised total dose [1][2][3]7,11]. The 2-year timepoint is predictive of the relative effects of randomised groups at longer follow up, even though the absolute rate of adverse effects continues to rise for at least a decade and probably for life [7,22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Change in photographic breast appearance at 2 years was used to define the late adverse effect caused by radiotherapy in this study. This endpoint has been well established and validated in randomised clinical trials, indicating it to be sensitive to small (<10%) differences in randomised total dose [1][2][3]7,11]. The 2-year timepoint is predictive of the relative effects of randomised groups at longer follow up, even though the absolute rate of adverse effects continues to rise for at least a decade and probably for life [7,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy and Oncology 104 (2012) 143-147 The routine use of hypofractionation in breast radiotherapy is supported by outcome data of four large randomised clinical trials in women with early breast cancer [1][2][3][4][5][6][7]. Residual concerns include the impact of dose inhomogeneity on the risk of adverse effects after hypofractionated schedules, so-called 'treble trouble' [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to have a study that will improve care without increasing complications. Randomized studies in breast cancer have shown that delivery can be given in a shorter period of time without effect on overall survival, local control or toxicities compared to standard fractionation (Haviland et al, 2013, Whelan et al, 2010, Owen et al, 2006). Similar findings are being reported in prostate cancer (Kupelian et al, 2007, Hoffman et al, 2014, Pollack et al, 2013).…”
Section: High Priority Topics For Lmicsmentioning
confidence: 99%
“…The underlying cell and molecular processes that explain these differences are not clear, but a mechanistic understanding is not needed to apply the linear-quadratic model safely and effectively. Over the last 20 years, several randomized trials involving a combined total of >7,000 women compared hypofractionated adjuvant radiotherapy to a standard regimen of 50 Gy in 25 fractions (Tables 1 and 2) (14)(15)(16)(17)(18)(19). UK Royal Marsden Hospital/Gloucestershire Oncology Centre (RMH/GOC) and Standardisation of Breast Radiotherapy Trial A (START A) trials tested two dose levels of a 13-fraction regimen in terms of late adverse effects and tumor control; the study design allowed direct estimates of a/b for each trial (15)(16)(17).…”
Section: What Recent Trials Showmentioning
confidence: 99%
“…Over the last 20 years, several randomized trials involving a combined total of >7,000 women compared hypofractionated adjuvant radiotherapy to a standard regimen of 50 Gy in 25 fractions (Tables 1 and 2) (14)(15)(16)(17)(18)(19). UK Royal Marsden Hospital/Gloucestershire Oncology Centre (RMH/GOC) and Standardisation of Breast Radiotherapy Trial A (START A) trials tested two dose levels of a 13-fraction regimen in terms of late adverse effects and tumor control; the study design allowed direct estimates of a/b for each trial (15)(16)(17). Based on a combined total of 278 local-regional tumor relapses in the two trials, the adjusted a/b value for tumor control was 4.6 Gy (95% (14,19).…”
Section: What Recent Trials Showmentioning
confidence: 99%